Linking smallholder farmers to markets in East Africa : Empowering mountain communities to identify market opportunities and develop rural agroenterprises - Sanginga, Pascal C.; Best, R.; Chitsike, C.; Delve, Robert J.; Kaaria, Susan K.; Kirkby, Roger A. (International Mountain Society (IMS) and United Nations University, 2004)
The livelihoods of mountain farmers are often constrained by poor access to markets and limited entrepreneurial skills for adding value to produce. Research and development organizations have now recognized that improving market access and enhancing the ability of resource-poor mountain farmers to diversify their links with markets are among the most pressing challenges in mountain agriculture. What is not so obvious is how to link small-scale farmers in marginal areas to growth markets, and how to develop methods and approaches that effectively integrate research, market access and development of community agroenterprise. The present article highlights the key steps and procedures in building capacity among farmers, farmers' groups, and communities to identify and evaluate market opportunities, develop profitable agroenterprise, and intensify production, while sustaining the resources upon which livelihoods depend. This approach, known as Participatory Market Research (PMR)—a component of the Enabling Rural Innovation (ERI) initiative—is being implemented and further refined by the International Centre for Tropical Agriculture (CIAT) in collaboration with research and development partners in Uganda, Malawi, and Tanzania.